Non-Classical Resource Approach as A Strategy for The Internationalization of Enterprises: Objectives Against General Obstacles - PopÅ‚awski, Åukasz; Szymczyk, Katarzyna (International Journal of Engineering and Technology, 2018)
The authors of the paper discuss the basic foundations of internationalization of private enterprise,Â related concepts of international business management, as well as key determinants and tendencies prevailing in contemporary realities of business management in global conditions. The main objective of the paper is to analyze the issues concerning the operation of enterprises in the international environment based on the concept of non-classical resource approach. The authors focus on interpreting the elementary categories of strategic management in relation to the phenomenon of internationalization, external and internal factors affecting the internationalization of enterprises, and, in terms of the non-classical resource approach, they evaluate to what extent the owned or required resources may determine the functioning of the company in the foreign markets.Â Â